Activation – Innovation – Acculturation. (Glotto)Didactics and the Migration Crisis – The Essence of the Issues (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The article was divided into two parts. The first one discusses the issue of emigration and its important social conditions. Important issues in the context of emigration were explained – activation, innovation, acculturation, and attention was paid to the essence of intercultural communication. The second part referred to the articles included in the post-conference volume – each of them was shortly summarized.